Exploration and Application of Emotional Interactive Design in Game Design - Weng, Weihang (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper aims to explore the application of emotional interaction design in game design and analyze its influence on game experience. Emotional interactive design takes emotion and emotional experience as the core of design, and strives to create richer and deeper user experience through various technical means and design strategies. In the field of game design, the research and application of emotional interactive design are relatively few, and its potential and value need to be tapped. This paper analyzes and discusses the basic concept and principle of emotional interaction design, emotional interaction in game design and its specific application in games, thus revealing the importance and potential of emotional interaction design in game design. Through case analysis and future prospect, this paper provides useful enlightenment and reference for further exploring the application of emotional interaction design in game design.